Medium and long latency EMG responses in leg muscles: Parkinson's disease. Issue 1 (January 1987) - Scholz, E; Diener, H C; Noth, J; Friedemann, H; Dichgans, J; Bacher, M
Abstract : Short, medium, and long latency EMG responses to muscle stretch from triceps surae and anterior tibialis muscles were recorded in normals and in 33 patients with Parkinson's disease. The latencies of all EMG responses except short latency were normal in patients with Parkinson's disease. The integrals of the medium latency responses in the stretched triceps surae muscle were significantly increased in patients. This result indicates a modulatory influence of the basal ganglia on medium latency EMG responses.